Innovative Approaches for Sustainable Wastewater Resource Management - Ayşe Ulusoy; Atılgan Atılgan; Roman Rolbiecki; Barbara Jagosz; Stanisław Rolbiecki (Agriculture, 2024)
Sustainable wastewater management is essential for conserving water resources and reducing environmental pollution. Traditional wastewater treatment methods primarily aim to purify water for reuse, yet they often involve high energy consumption, extensive chemical use, and loss of potentially recoverable resources, which pose sustainability challenges. With approximately 2.2 billion people worldwide currently lacking access to clean water—a number projected to exceed 3 billion by 2025—water scarcity has become an urgent issue. Traditional wastewater treatment processes handle around 330 billion cubic meters of water annually; however, they account for 3–4% of global energy consumption and produce 300 million tons of carbon emissions. This situation underscores the need for more sustainable treatment methods. Innovative wastewater treatment technologies have the potential to facilitate the reuse of approximately 50 billion cubic meters of water each year, helping to alleviate water scarcity. Additionally, energy recovery from these processes aims to achieve an annual energy savings of 20 TWh, in contrast to conventional treatment methods. This article examines recent advances in sustainable wastewater management technologies, specifically focusing on biological, physicochemical, and membrane-based processes. It discusses strategies for optimizing these processes to minimize environmental impact. Furthermore, innovative approaches, such as advanced oxidation processes and energy recovery, are explored for their potential to harness energy and recover nutrients from wastewater. The article concludes that implementing innovative strategies in sustainable wastewater management can significantly contribute to water conservation, energy savings, and a reduction in carbon footprint.